Gender equality and social inclusion in focus: key insights from Solar Irrigation for Agricultural Resilience (SoLAR) - Agarwal, Tripti; Ravindranath, Darshini (International Water Management Institute, 2026)
Gender Equality and Social Inclusion in Focus presents evidence from the Solar Irrigation for Agricultural Resilience (SoLAR) project (2020–2025), implemented across India, Bangladesh, Nepal, and Pakistan, to examine how inclusive approaches can advance equitable and climate-resilient agricultural development in South Asia. The report situates its analysis within persistent structural barriers faced by rural women and marginalized communities, including limited land ownership, constrained access to finance, and exclusion from water and energy governance.